Analyzing the Implementation of Medical Workers’ Rights Policy in a Public Hospital: Evidence from Tanjungpinang City through the Edwards III Theory - Tessa Citrani; Nur Ilmiah Rivai; O. Okparizan (Golden Ratio of Law and Social Policy Review, 2026)
Medical personnel are strategic actors in the healthcare system who face heavy workloads, legal risks, and complex professional demands, making the protection of their rights essential. This study analyzes the implementation of policies on the fulfillment of medical personnel’s rights under Article 721 of Government Regulation Number 28 of 2024 at RSUD Kota Tanjungpinang. Using a descriptive qualitative approach within a constructivist paradigm, data were collected through in-depth interviews, document analysis, and internal hospital regulations. The data were analyzed using the Miles, Huberman, and Saldaña interactive model and interpreted through the Edwards III policy implementation framework. The findings show that the fulfillment of medical personnel’s rights has been carried out normatively and administratively, but remains not fully optimal in practice. Basic rights, such as social security and occupational safety, are relatively well fulfilled, while strategic rights particularly legal protection, fair compensation, professional recognition, and career development opportunities still face challenges. Key obstacles include limited policy communication, budget and human resource constraints, varying commitment among implementers, and bureaucratic structures that have not fully supported institutional protection. This study concludes that effective fulfillment of medical personnel’s rights requires not only adequate regulations but also stronger institutional capacity and policy implementation at the hospital level.